Jamu 2005 a feast for the sense - Akademi Seni Budaya dan Warisan Kebangsaan ([Kuala Lumpur] : ASWARA, 2005)
Contemporary dance presentation by : pt.1. Choo Tee Kuang, Suhaimi Magi, Wong Kit Yaw (1 hr. 24 min.) - pt.2.Aris Kadir, Loke Soh Kim, Umesh Shetty (1 hr.05 min.) - pt.3. Gan Chih Pei, Mew Chang Tsing, Joseph Gonzales (1 hr. 09 min.).
Hoi Cheng Sim in memory by Wong Kit Yaw.
Choo Tee Kuang, Suhaimi Magi, Wong Kit Yaw, Aris Kadir, Loke Soh Kim, Umesh Shetty, Gan Chih Pei, Mew Chang Tsing, Joseph Gonzales .
DVD format.
Keywords: Dance -- Malaysia; Performing arts; Modern dance